DNA extraction from primary liquid blood cultures for bloodstream infection diagnosis using whole genome sequencing. Issue 3 (March 2018) - Anson, Luke W.; Chau, Kevin; Sanderson, Nicholas; Hoosdally, Sarah; Bradley, Phelim; Iqbal, Zamin; Phan, Hang; Foster, Dona; Oakley, Sarah; Morgan, Marcus; Peto, Tim E. A.; Crook, Derrick W.; et al.
Abstract : Purpose. : Speed of bloodstream infection diagnosis is vital to reduce morbidity and mortality. Whole genome sequencing (WGS) performed directly from liquid blood culture could provide single‐assay species and antibiotic susceptibility prediction; however, high inhibitor and human cell/DNA concentrations limit pathogen recovery. We develop a method for the preparation of bacterial DNA for WGS‐based diagnostics direct from liquid blood culture. Methodology. : We evaluate three commercial DNA extraction kits: BiOstic Bacteraemia, Amplex Hyplex and MolYsis Plus. Differential centrifugation, filtration, selective lysis and solid‐phase reversible immobilization bead clean‐up are tested to improve human cells/DNA and inhibitor removal. Using WGS (Illumina/MinION), we assess human DNA removal, pathogen recovery, and predict species and antibiotic susceptibility inpositive blood cultures of 44 Gram‐negative and 54 Staphylococcus species. Results/Key findings. : BiOstic kit extractions yield the greatest mean DNA concentration, 94‐301 ng μl −1, versus 0‐2.5 ng μl −1 using Amplex and MolYsis kits. However, we note higher levels of inhibition (260/280 ratio 0.9‐2.1) and human DNA (0.0‐4.4×10 6 copies) in BiOstic extracts. Differential centrifugation (2000 g, 1 min) prior to BiOstic extraction reduces human DNA by 63‐89 % with selective lysis minimizing by a further 62 %. Post‐extraction bead clean‐up lowers inhibition. Overall, 67 % of sequenced samples (Illumina MiSeq) contain <10 % human DNA, with >93 % concordance between WGS‐based species and susceptibility predictions and clinical diagnosis. If >60 % of sequencing reads are human (7/98 samples) susceptibility prediction becomes compromised. Novel MinION‐based WGS ( n =9) currently gives rapid species identification but not susceptibility prediction. Conclusion. : Our method for DNA preparation allows WGS‐based diagnosis direct from blood culture bottles, providing species and antibiotic susceptibility prediction in a single assay.